2020
DOI: 10.1371/journal.pone.0227876
|View full text |Cite
|
Sign up to set email alerts
|

Promising antifungal activity of new oxadiazole against Candida krusei

Abstract: Candida krusei is one of the most common agents of invasive candidiasis and candidemia worldwide, leading to high morbidity and mortality rates. This species has become a problem due to its intrinsic resistance and reduced susceptibility to azoles and polyenes. Moreover, the number of antifungal drugs available for candidiasis treatment is limited, demonstrating the urgent need for the discovery of novel alternative therapies. In this work, the in vivo and in vitro activities of a new oxadiazole (LMM11) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…In this study, we demonstrated a more promising effect of LMM6, as compared to others 1,3,4-oxadiazoles previously tested in our laboratory [ 21 , 22 , 23 ]. The LMM6 antifungal activity in vitro clearly reveals reduction in the number of C. albicans viable cells (CFU quantitative analysis) in which it was confirmed by growth decrease by CFM.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In this study, we demonstrated a more promising effect of LMM6, as compared to others 1,3,4-oxadiazoles previously tested in our laboratory [ 21 , 22 , 23 ]. The LMM6 antifungal activity in vitro clearly reveals reduction in the number of C. albicans viable cells (CFU quantitative analysis) in which it was confirmed by growth decrease by CFM.…”
Section: Discussionsupporting
confidence: 53%
“…Additionally, it is absent in humans, that can contribute with the development of selective drugs against pathogens [ 25 ]. 1,3,4-oxadiazole-based drugs have been widely studied by researchers [ 21 , 22 , 23 , 26 , 27 , 28 , 29 ]. These compounds have a high therapeutic power and broad spectrum of action, such as anticancer, antifungal, antibacterial, antitubercular, anti-inflammatory, antineuropathic, antihypertensive, antihistaminic, antiparasitic, antiobesity, antiviral activity, among others [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research using the thioredoxin system as a target for treatment for fungal infections has increased in recent years [ 97 , 114 , 126 , 127 , 128 , 129 , 130 , 131 ]. The identification of essential genes is a strategy that elucidates new targets for antifungal therapy, and when widely conserved in fungi, there is an increased interest in acting as new targets for drug design [ 97 ].…”
Section: Search For New Therapeutic Options—a Journeymentioning
confidence: 99%
“…The inhibitory activity in vitro was 64.9 μM, without cellular toxicity and, most importantly, significantly reduced the fungal burden on the kidneys of mice in the candidemia experimental model [ 128 ]. One of these oxadiazole compounds, named LMM11, showed activity against C. krusei with MICs ranging from 65 to 129.9 μM, and it also succeeded in reducing colony-forming unit (CFU) recovered from the kidneys of infected mice with this clinically-relevant pathogen, mostly involved in hospital infections [ 130 ]. The two oxadiazoles (LMM5 and LMM11) selected against TRR1 showed a range of inhibitory action from 2.03 to 71.99 μM against nine isolates of Paracoccidioides spp.…”
Section: Search For New Therapeutic Options—a Journeymentioning
confidence: 99%